PENGARUH PENGGUNAAN PUPUK UREA DAN APLIKASI HERBISIDA PRA-TUMBUH TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell.Arg.) DAN GULMA DI PEMBIBITAN - Yakup Parto; Yernelis Syawal; Teguh Achadi (Universitas Trunojoyo Madura, 2012)
A Research was carried out at green house of Agriculture Faculty of Sriwijaya University from October 2010 to January 2011 using split-split plot design. Main plot were pre-emergence herbicides : H0 = no preemergence herbicide treatment (control), H1 = preemergence herbicide of methyl metsulfuron, and H2 = preemergence herbicide of ametryn. Subplot were dose of urea fertilizers : U0 = no urea fertilizer treatment (control), U1 = 2 gram of urea fertilizer per plant, and U2 = 4 gram of urea fertilizer per plant. Sub-sub plot were preemergence dosages : D0 = 0 liter formulation per ha, D1 = 1,5 liter formulation per ha, and D2 = 3,0 liter formulation per ha. Parameters measured were diameter of sleep eye stum, time of bud emergence, height of bud, number of leaves, percentage of growth seedling, weed growth, and efficiency of weed control. Results showed that kind of preemergence herbicides, urea fertilizer dosages, and preemergence herbicide dosages were no significant effect to weed dry weight due to weed growing were relative small. This supposed because soil which used as growth media no enough contain weed propagule, so the following research are need conducted.